Marta Camilla Wright. 2023. Saved and Healed. Illness, Illness Causation and Healing Among Ethiopian Orthodox Christians at Holy Water Sites in Addis Ababa - Katharina Wilkens (DIN)
[AI generated] Katharina Wilkens reviews Marta Camilla Wright’s dissertation "Saved and Healed, an ethnographic study of healing practices at holy water sites in Addis Ababa". Wright explores how illness is understood and treated through Orthodox Christian rituals involving holy water, prayer, and sacred objects. Illness is framed both biomedically and spiritually, with healing achieved through relationships among people, places, spirits, and God. While the study’s theoretical scope is somewhat limited, its rich ethnographic detail and reflections on materiality, space, and ritual make it a valuable contribution. It fills a significant gap in research on contemporary Orthodox Christian healing in Ethiopia.